2018
DOI: 10.3389/fphys.2018.00803
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Mitochondrial FoF1-ATP Synthase as the Target of the Immunomodulatory Drug Bz-423

Abstract: Targeting the mitochondrial enzyme FoF1-ATP synthase and modulating its catalytic activities with small molecules is a promising new approach for treatment of autoimmune diseases. The immunomodulatory compound Bz-423 is such a drug that binds to subunit OSCP of the mitochondrial FoF1-ATP synthase and induces apoptosis via increased reactive oxygen production in coupled, actively respiring mitochondria. Here, we review the experimental progress to reveal the binding of Bz-423 to the mitochondrial target and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Several lines of evidence support the idea that the mechanism of flexible coupling is conserved across all types of rotary ATP synthases: 1) the structure and polypeptide sequences of b, g, and OSCP subunits involved in this process are highly conserved; 2) a canonical OSCP (or δ in chloroplasts and bacteria) is found in all three lineages of ATP synthase known to have independently acquired novel peripheral stalk components (28,29); 3) a cryo-EM study of bovine ATP synthase (11) identified rotary substates of this complex, albeit at lower resolution, indicating rotation of F 1 relative to the remainder of the complex. Re-evaluating these results in light of our data, they do in fact show concerted rotation of F 1 with the central stalk; 4) well-known inhibitors and regulators of ATP synthase bind to OSCP, affecting the catalytic rate and K M (21,30), suggesting a mechanistic rather than merely structural role for this subunit.…”
Section: Rotary Substates Reveal Concerted Rotation Of F 1 and Centrasupporting
confidence: 61%
“…Several lines of evidence support the idea that the mechanism of flexible coupling is conserved across all types of rotary ATP synthases: 1) the structure and polypeptide sequences of b, g, and OSCP subunits involved in this process are highly conserved; 2) a canonical OSCP (or δ in chloroplasts and bacteria) is found in all three lineages of ATP synthase known to have independently acquired novel peripheral stalk components (28,29); 3) a cryo-EM study of bovine ATP synthase (11) identified rotary substates of this complex, albeit at lower resolution, indicating rotation of F 1 relative to the remainder of the complex. Re-evaluating these results in light of our data, they do in fact show concerted rotation of F 1 with the central stalk; 4) well-known inhibitors and regulators of ATP synthase bind to OSCP, affecting the catalytic rate and K M (21,30), suggesting a mechanistic rather than merely structural role for this subunit.…”
Section: Rotary Substates Reveal Concerted Rotation Of F 1 and Centrasupporting
confidence: 61%
“…Several lines of evidence support the idea that OSCP-mediated flexible coupling plays a role in other F-type ATP synthases: (i) The structure and polypeptide sequences of b, g, and OSCP subunits involved in this process are highly con-served. (ii) An OSCP subunit (or d in chloroplasts and bacteria) is found in all three lineages of ATP synthase known to have independently acquired novel peripheral stalk components (24,25). (iii) A cryo-EM study of bovine ATP synthase (11) identified rotary substates of this complex, albeit at lower resolution, indicating rotation of F 1 relative to the remainder of the complex.…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimermentioning
confidence: 99%
“…Reevaluating these results in light of our data, they do in fact show concerted rotation of F 1 with the central stalk. (iv) Well-known inhibitors and regulators of ATP synthase bind to OSCP, affect-ing the catalytic rate and Michaelis constant (K M ) (26,27), suggesting a mechanistic rather than merely structural role for this subunit. The simpler bacterial and chloroplast ATP synthases have a thinner, flexible peripheral stalk relative to Polytomella, and previous cryo-EM studies have found substantial flexibility in the peripheral stalk even between primary rotary states (12)(13)(14).…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimermentioning
confidence: 99%
“…OSCP connects F O with F 1 through the peripheral stalk and is an important site of modulation of ATP synthase leak channel activity due to its interaction with different endogenous and pharmacological inducers of mPTP [80][81][82]. During the mPT initiation step, mPTP modulators bind directly to different ATP synthase subunits: CypD binds to OSCP subunit [83][84][85] and Ca 2+ binds to β subunit [63,64] ( Fig. 1a).…”
Section: The Molecular Composition Of Mptp: Atp Synthase C-subunit Rimentioning
confidence: 99%